Análise das decisões do CADE em atos de concentração econômica envolvendo empresas atuantes no setor de geração de energia elétrica no Brasil - Paula, Renan Gabriel de (Universidade Federal de São Carlos, 2025)
The Brazilian electricity sector is characterized as a capital-intensive industry composed of specific assets (Dontal, 2012), and is understood to be a strategic system essential to the functioning of various economic activities (Bacellar; Gonçalves, 2021). With regard specifically to the power generation market, the strong presence of private initiative stands out, evidenced by the large number of operational projects, which reflects the entry of independent producers and the encouragement of competition (Pessoa, 2022). Despite this, a significant concentration of installed capacity remains under state control (Albuquerque, 2009). Projections for the coming years indicate the expansion of the national energy matrix, with a predominance of renewable sources (EPE, 2025). In this context, the present study aims to examine how the Administrative Council for Economic Defense (CADE) analyzed merger cases in the electricity generation market decided between 2020 and 2024. It was found that most of these transactions were approved without restrictions, with the fast-track review procedure being predominantly applied. The case evaluated under the ordinary procedure was also approved without restrictions, with CADE following the steps outlined in its Guidelines and conducting a thorough analysis regarding the potential exercise of market power after the transaction.
Analysis of CADE's decisions in merger control cases involving companies operating in the electricity generation sector in Brazil.
Keywords: Geração de energia; Ato de concentração; CADE; Power Generation; Merger; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL::ORGANIZACAO INDUSTRIAL E ESTUDOS INDUSTRIAIS; 9. Indústria, Inovação e Infraestrutura